Study on Threshold Selection Methods in Calculation of Ocean Environmental Design Parameters - Liu, Guilin; Gao, Zhikang; Chen, Baiyu; Fu, Hanliang; Jiang, Song; Wang, Liping; Kou, Yi (IEEE access, 2019)
In marine engineering design, the threshold selection is a basic and very important part for the analysis of measured data and subsequent acquisition of sample data for probability analysis. In this paper, threshold selection methods are deeply studied from the two perspectives of time domain and frequency domain, and the obtained calculation results with different thresholds are provided. First, the theory of mean residual life plot is used to quantify the threshold value of the measured tide levels of Hangzhou Bay. For the 100-year return periods design values calculated in the Gumbel distribution, the results under the threshold u = 3.9 m shows an increasing of 1.70% over those under the threshold u = 3.75 m; and the results under the threshold u = 3.75 m shows an increase of 0.97% over those under the threshold u = 3.5 m. The quantitative selection method of a threshold is simple and practical, and eliminates the tedious process of multiple trials based on empirical threshold determination. Besides, for the first time, the coherence spectrum threshold is used to explore the significant correlations of different tide level sequences in the frequency domain. Based on the threshold selection method used in the WOSA method-based coherence spectrum significance test, the coherence spectrum thresholds of different tide level in Hangzhou Bay are provided to effectively avoid the false identification of false peaks. It is suggested by the calculation results that, at the overlapping ratio of 50%, the segment number of three and the segment length of 16, and the spectral analysis shows that the extreme tide level of Hangzhou Bay has a vibration period of 21.3 years.